Lectin galactoside-binding soluble 3 binding protein mediates methotrexate resistance in choriocarcinoma cell lines. Issue 2 (1st February 2022) - Chen, XiaoJing; Xue, Yite; Wang, Lingfang; Weng, Yang; Li, Sen; Lü, Weiguo; Xie, Xing; Cheng, Xiaodong
ABSTRACT: Choriocarcinoma is one of the most aggressive gestational trophoblastic neoplasias (GTN). Methotrexate (MTX) resistance is the main cause of treatment failure in choriocarcinoma. However, the mechanism of MTX resistance in choriocarcinoma is poorly known. This study aims to explore the function of Lectin galactoside-binding soluble 3 binding protein (LGALS3BP) in MTX-resistance in choriocarcinoma cells. Gradual dose escalation of MTX was used to establish MTX-resistant choriocarcinoma cells (JAR-MTX and JEG3-MTX cell lines). RNA-sequencing was used to explore the differentially expressed genes. Plasmids or SiRNA transfection was used to regulate the expression of LGALS3BP. ELISA was used to detect the concentrations of LGALS3BP in the serum of MTX-sensitive and MTX-resistant patients. qRT-PCR, Western blot, and CCK-8 assay were used to determine the effects of LGALS3BP on MTX-resistance in JAR and JEG3 cells. The results showed the relative resistance index (RI) of MTX is 791.50 and 1040.04 in JAR-MTX and JEG3-MTX, respectively. LGALS3BP was up-regulated in MTX-resistant cells compared to original cells in both RNA and protein level. The concentrations of LGALS3BP were higher in the sera of MTX-resistant patients than in MTX-sensitive patients. Knocking down LGALS3BP can reverse the MTX-resistance in JAR-MTX and JEG3-MTX cells. In summary, we preliminarily established two MTX-resistant cells, and performed RNA-sequencing, and found LGALS3BP may play important role in MTX-resistance. Our work not only provides a research tool (MTX-resistant cells) for other researchers, but gives some hint on how MTX resistance is regulated.